Management Of Recurrent Aphthosal Stomatitis (SAR) Cases Through A Communication, Information And Education (KIE) Approach - Fauzia Nur Maulida; Naviatullaily Yarsiska (International Journal of Health Engineering and Technology, 2026)
Recurrent aphthosis stomatitis (SAR) is a common inflammatory condition of the oral cavity characterized by a round or oval ulcer with a yellowish-white color with erythema edges and occurs repeatedly. SARs can be classified into 3 types based on their number and size, namely minor SAR, major SAR, and herpetiform SAR. Factors that can cause SAR are in the form of hematology, genetics, immunology and hormonal. To determine the management of cases of Recurrent Aphthosal Stomatitis (SAR) et causa stress and nutritional deficiency through the KIE approach. A 23-year-old man came with a complaint of canker sores on the buccal mucosa of the right upper jaw. The patient complained of canker sores since 3 days ago and the complaints recur about once every 2-3 months. On intraoral examination, there was an oval-shaped ulceration, clearly bordered, white base and surrounded by erythema halo, measuring 3x2 mm on the buccal mucosa of the right upper jaw and symptomatic. Patients are given multivitamin supplements and focus more on the provision of Communication, Information and Education (KIE). Patients are given information about the triggering factors that can cause SAR, namely due to psychological stress. Patients are also given education about oral hygiene, increasing mineral water consumption, consuming vegetables and fruits and managing stress. An approach through Communication, Information and Education (KIE) and psychological support for SAR sufferers due to stress factors is more effective, such as directing patients to manage their stress management with a healthier lifestyle and diet to accelerate the healing process of lesions. If needed, patients can be referred to a psychologist/psychiatrist for psychological support.